Multiply (x+3)(x−2)

.(1 point)
Responses

x2+x−6
x squared plus x minus 6

x2−5x+6
x squared minus 5 x plus 6

x2−6
x squared minus 6

x2+5x+6

1 answer

To multiply the expression \( (x+3)(x-2) \), you can use the distributive property (also known as the FOIL method for binomials):

  1. First: \( x \cdot x = x^2 \)
  2. Outer: \( x \cdot (-2) = -2x \)
  3. Inner: \( 3 \cdot x = 3x \)
  4. Last: \( 3 \cdot (-2) = -6 \)

Now, combine all these terms:

\[ x^2 - 2x + 3x - 6 \]

Combine the like terms:

\[ x^2 + (3x - 2x) - 6 = x^2 + x - 6 \]

So, the final result is:

\[ \boxed{x^2 + x - 6} \]

Therefore, the correct response is x² + x - 6.